OnabotulinumtoxinA is now an important tool for managing pediatric neurogenic lower urinary tract dysfunction - Frainey, Brendan T.; Clayton, Douglass B. (Frontiers in Pediatrics, 2024)
Initial urologic management of pediatric neurogenic lower urinary tract dysfunction (NLUTD) includes clean intermittent catheterization (CIC) regimen and use of anticholinergic or beta3 agonist medications. Historically, NLUTD that did not respond to these initial management strategies received open surgical procedures such as augmentation cystoplasty (AC) to increase bladder capacity and create a lowerpressure reservoir. Since its first reported use in 2002, intradetrusor onabotulinumtoxinA (BTX-A) injections has developed an emerging role in management of pediatric NLUTD, culminating in its recent FDA-approval in 2021. In this review, the current evidence regarding the safety, tolerability, and efficacy of BTX-A use in pediatric NLUTD will be summarized. Additionally, we will attempt to define the current role of BTX-A in the management of patients with NLUTD, discuss limitations to the current body of literature, and suggest future avenues of study.